Implementation of the Lisbon Strategy Targets at the Regional Level in the EU and Slovenia - Aleksander Aristovnik; Andrej Pungartnik (Central European Public Administration Review)
In 2000, the European Union set itself a target in the Lisbon Strategy to become the most dynamic, competitive and knowledge-based economy in the world in ten years, whereas during the mid-term review, which was held five years later, it redefined its two main objectives: creation of new and better jobs and achievement of stronger, lasting economic growth. This paper aims to study the current situation in the European Union and Slovenia regarding the implementation of the targets of the renewed Lisbon Strategy. The analysis focuses on establishing at what stage the EU is in the attainment of its goals and how successfully it has implemented the strategy at the regional level of the EU Member States. The basic tools in the analysis included the time-distance monitoring method and a presentation of the time lead or lag in the implementation of the selected Lisbon Strategy targets at the NUTS 2 regional level of the enlarged EU and Slovenia.